A Review on Pharmaceutical Potential of Parthenium Plant (Asian Journal of Pharmaceutics (AJP), 2020)
Parthenium plant, in general, is known to be harmful, dangerous, and invasive in nature. It causes much economicloss to farmers by affecting the cultivation of crops and considered to be a threat to primary production of crops andbiodiversity as well. Parthenium hysterophorus a weed belonging to the family Asteraceae, it is an erect short-livedplant and is known for its fleshy growth along sides of abandoned places, roadsides, and uncultivated lands. Thisweed is found in hot and humid climates around the globe. This invasive species is known with different names indifferent countries such as carrot weed, star weed, congress grass, wild feverfew, ragweed, bitter weed, and whitetop. The spread of P. hysterophorus has been found to cause enormous loss to biodiversity by replacing naturalecosystems and sometimes known to cause total habit alternation. In this review article, we discuss P. hysterophorusas a weed, its origin, reproductive bionomics, chemical composition, and its pharmaceutical potential as antibacterial,anti-inflammatory, hypoglycemic, anti-HIV, and antitumor activity in detail.